(untitled) (Research, Society and Development, 2016)
We investigated with the students of a higher education course in a private University of the state of São Paulo, to identify fragments of his views on the notion of function. We identify the semiotic representation registers as Duval (1995) and categorized according to Bogdan and Biklen (1994). Our findings allow us to conclude that we should invest more in semiotic representations, providing a more effective teaching work in the construction of the meaning of the concept of function.